Neo-Sumerian Account Texts in the Horn Archaeological Museum - Sigrist, M. (1988)
= AS VI; p.73-99: Seal Impressions on the Ur III Tablets in the Collections of the Siegfried H. Horn Archaeological Museum at Andrews University by Carney E.S. Gavin, Diana Stein, and Constance Menard